TRANSLATION OF PHRASEOLOGICAL UNITS THROUGH THE PRINCIPLE OF COMPENSATION: THEORETICAL AND PRACTICAL ANALYSIS (International conference on multidisciplinary science, 2025)
This paper explores the principle of compensation as a pivotal strategy in the translation of phraseological units, emphasizing its theoretical foundations and practical application. Using materials drawn from Uzbek and German mass media, the study investigates how semantic integrity, imagery, cultural adaptation, and pragmatic functions are preserved in cases where direct equivalents are unavailable. The analysis provides comparative examples demonstrating the use of equivalence, adaptation, and especially compensation strategies, highlighting their effectiveness in maintaining both semantic content and emotional impact.